Analisis Kebutuhan Pengembangan Buku Siswa Berbasis Pendekatan STEM pada Pembelajaran Fisika dalam Menghadapi Era Revolusi Industri 4.0 - Pratiwi, Yulia; Ramli, Ramli (Jurnal Penelitian Pembelajaran Fisika, 2019)
Physics learning aims to make students have a scientific attitude, master the concepts of        science, and understand phenomena that occur in everyday life. Learning physics by applying the STEM approach can improve the skills needed by students. The STEM approach can train students to be able to integrate Science, Technology, Engineering and Mathematics in learning physics. The     implementation of the STEM approach in learning physics can be supported by the existence of    teaching materials that are appropriate to the needs and characteristics of students. One form of teaching material that can support independent learning is student books. However, there are still student books that have not fully facilitated the implementation of the STEM approach in learning physics. This study aims to analyze the needs of student books based on the STEM approach in    learning physics. This research is a descriptive study conducted through observation at senior high school (SMA N 4 Padang) with a sample of research is students of 11th grade. Analysis of student book needs based on the STEM approach, including student analysis, analysis of learning activities,      analysis of graduate competency standards, and assessment analysis. The instruments used in this study were in the form of questionnaires and interview sheets. The results showed that the analysis of learners obtained an average value of 67.54, analysis of learning activities obtained an average value of 72.91, analysis of graduate competency standards obtained an average value of 74.60 and analysis of the assessment obtained an average value of 84,24. Therefore, it is necessary to develop physics teaching materials in the form of student books based on the STEM approach